A Study of Flexural and Bending Strength of Steel, Polypropylene and Hybrid Fibre Reinforced Concrete without Adding Admixture - Tamil Selvi, M; A K, Dasarathy; S. Thandavamoorthy, T; ., FIE; Arb, FIIT; PonkumarIlango, S (International Journal of Engineering and Technology, 2018)
The present study has been taken up for evaluating the different types of concrete. Emphasis has been given to the strength and deformation properties of reinforced concrete beams.Â ThisÂ paperÂ presentsÂ theÂ resultsÂ ofÂ anÂ experimental investigation carried out on four different types reinforced concrete beams, 150 mmÂ Ã— 150Â mmÂ Ã— 700 mm in size. The beams were tested under one-third point loading. The results exhibited that the flexural strength of concrete are meaningfully improved by addingÂ steel, polypropylene and hybrid fibers.Â Out of the three different types of fibers used in this study, the fibers with steel and hybrid showed better efficiency in improving the flexural response.Â Â